أثر قاعدتي لا ضرر ولا ضرار وتقييد المباح في تعدد الزوجات قطاع غزة أنموذجا - بياري، سهاد حسن حسن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research aims to shed light on the effect of two principles: “No harm and no reciprocated harm” as well as “The restriction of permissibility regarding polygamy.” The model and focus of the research is the Gaza Strip in Palestine wherein the researcher intensively examined the two principles concerning polygamy. She presents the problems associated with polygamy before discussing them in more depth. It is evident to her that the problems are not actually related to polygamy in and of itself. But, is actually the stem problems from crooked society and its culture. The researcher introduces the laws and legislations put in place by some of the Muslim countries regarding polygamy, on the basis of preventing and limiting the many complications associated with it. It is also apparent to her that a substantial number of these laws are aimed at completely banning polygamy, or to a lesser extent, openly restricting it. As a result, the society does not have permissible (halal) alternatives when they are critically needed. To add to that; the laws and legislations enforced by some of the countries are put in place to bluntly ban polygamy, rather than mend the reality of such practice. The researcher referred to both, the descriptive approach and the inductive method, to examine the mentioned issues. She got her insight by distributing a public questionnaire that enabled her to know the Gazans' views on polygamy. It is important to note the different views that arise among the Gazans regarding polygamy. For those who look at the narrower picture of polygamy concerning the current wife, the magnitude of problems and the extent of impact of such marriage leads them to blindly take an opposing stance on polygamy. It is the people who look at the bigger picture، concerning the millions of unmarried women in our Islamic world that tend to support such a cause. On the basis of weighing in the possible benefits and downfalls of this contemporary issue, no two people can have the same point of view. The scale of the benefits and downfalls tends to swing up and down، depending on the person and their point of view. The researcher establishes a set of means and suggestions for individuals and institutions in the Gaza Strip to enable them to work collectively to reform the reality of polygamy.